Field Performance and Genetic Analysis in Some Advanced Lines of Mustard (Brassica rapa L.) (The Agriculturists, 2016)
Twenty four genotypes including four check varieties of mustard (Brassica rapaL.) were collected for estimating the genetic variability, heritability, genetic advance of different characters related to the yield and yield components. The experiment was conducted at the Sher-e-Bangla Agricultural University research farm, Dhaka during 2013-2014. Days to 50% flowering and days to 80% maturity showed moderate difference between the phenotypic and genotypic variance whereas, minimum differences were found in number of primary branches  plant-1, number of secondary branches plant-1, number of seeds siliqua-1, siliqua length and thousand seed weight and yield plant-1.  Number of secondary branches plant-1 showed high heritability coupled with high genetic advance in percentage of mean. On the other hand, days to 50% flowering, no. of siliqua plant-1, yield plant-1 showed high heritability with moderate genetic advance in percentage of mean. Days to 80% maturity, no. of primary branches plant-1, no. of seeds siliqua-1 showed high heritability coupled with low genetic advance in percentage of mean. The study showed that variations in the extent of genetic variability, heritability and genetic advance in traits under study which can facilitate selection for further improvement of important traits of Brassica rapa L.The Agriculturists 2016; 14(1) 112-121